SUSTAINABLE FUTURE MOBILITY - Gandhi, Devendra Rajaram (Global journal of Business and Integral Security, 2023)
The transformational changes are going on in the field of mobility. The major focus in the transformational changes is to decarbonise of the mobility. The various technologies are under implementation and some under exploratory phase to decarbonise the mobility. The sustainable mobility approaches are there to reduce or minimize the greenhouse gas emission in the mobility sector. The various megatrends are evolved as future mobility. The future mobility is around centralized motorized mobility. The future mobility trends are projected toward the sustainable mobility but as per the past studies mobility is unsustainable. There is need to do research in area of sustainable future mobility. So, this research is concentrated on the “sustainable future mobility” and identified scope beyond the decorbanisation mobility. The individual mobility technology efforts are found to make future mobility sustainable. The sustainable mobility is not an individual effort but at central of other various sectors. The previous research and studies are found the need to integrate future mobility. But there is no detail research are available to integrate the sector or resources other than mobility in Indian context. There is limited research available to integrate the mobility technologies as intersectoral integration. The mobility is vast area in respect to country, region, continents, etc. So, to complete the study on time this research is focus on India. This research is focus on current decorbanisation status of mobility in India, identifying the sector or resource which need to integrate for sustainable future mobility. The research is done by designing the survey questions and feedback taken on same on scale of the 1 to 10. The sector for survey is selected considering the past research, direct connect to mobility ecosystem and common sectors. The survey has been taken by creating google form, direct interacting mobility sectors and other concern sector leader. The research results are indicated need to integrate the sectors or resource such as energy sector, human behavior, infrastructure, the commercial sector, government policies and schemes, technologies (digitalization, artificial intelligence) mobility as a service and the education sector. The important elements for economic model are identified in this research which important to implement the sustainable future mobility in India.